2010
DOI: 10.1007/s11255-010-9821-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between major adverse cardiac events and angiographic findings in dialysis patients

Abstract: This observational study confirms that in dialysis patients coronary atherosclerotic damage shown by angiography is strongly related to MACE and that age and severe CAD are major risk factors for MACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Experimental evidence regarding the impact of angiographically significant CAD on clinical event rates and long-term survival in patients with ESRD is lacking and observational studies have reported variable results (Table 1). Angiographic CAD has been documented to predict major adverse cardiac events (MACE) [39, 40, 50, 52] and has been associated with increased mortality [31, 48, 49]. Sharma et al [31] reported a significantly worse unadjusted 2-year survival among patients with angiographic CAD compared with patients with normal coronary arteries.…”
Section: Assessment Of Cadmentioning
confidence: 99%
“…Experimental evidence regarding the impact of angiographically significant CAD on clinical event rates and long-term survival in patients with ESRD is lacking and observational studies have reported variable results (Table 1). Angiographic CAD has been documented to predict major adverse cardiac events (MACE) [39, 40, 50, 52] and has been associated with increased mortality [31, 48, 49]. Sharma et al [31] reported a significantly worse unadjusted 2-year survival among patients with angiographic CAD compared with patients with normal coronary arteries.…”
Section: Assessment Of Cadmentioning
confidence: 99%
“…The poor correlation between positive angiograms and survival in our study also presents as an apparent contrast with the studies done on ESRD patients on transplant waiting list or posttransplant patients. 11 It can be explained by the positive impact of kidney transplant on patient survival even in high risk groups such as those with CAD, low number of patients in our study, and long-term nature of it. The above discussion however opens room of debate for predictive role of preoperative stress test or coronary angiogram widely employed as part of screening programs and risk stratification strategies in the United States and Europe on patient survival and occurrence of MACE.…”
Section: Discussionmentioning
confidence: 73%
“…In another short series of 63 patients, these results were confirmed with 49% of patients (including asymptomatic ones) having significant coronary artery disease. The author showed a relationship between coronary lesions and the cardiovascular events over a 5-year follow-up [ 32 ]. Screening for ischemia and treating it are thus major objectives before renal transplantation.…”
Section: Discussionmentioning
confidence: 99%